AccrowLive: A multiplatform telemetry and sonification solution for rowing - Cesarini, D.; Schaffert, N.; Manganiello, C.; Mattes, K. (Procedia Engineering, 2014)
Monitoring and measuring elite athletes in their natural training environment is attracting interest in the sporting and engineering research and users community. Complex and cumbersome measurement equipment can influence training and analysis sessions athletes undertake to improve their level of performance, but monitoring is only one of the steps to go along the way of athletic performance improvement. Real-time feedback represents a good way to improve the performance of the athletes, providing direct information about quality and not only quantity of movement. Sound is an effective means to provide a feedback to humans, and sonification is a way to functionally transform information into sound. In this paper we want to present an innovative ready-to-use telemetry and sonification solution for enhancement of rowing training.